2020
DOI: 10.3390/s20216182
|View full text |Cite
|
Sign up to set email alerts
|

A Sensor-Based Screening Tool for Identifying High Pelvic Mobility in Patients Due to Undergo Total Hip Arthroplasty

Abstract: There is increasing evidence that pelvic mobility is a critical factor to consider in implant alignment during total hip arthroplasty (THA). Here, we test the feasibility of using an inertial sensor fitted across the sacrum to measure change in pelvic tilt, and hence screen for patients with high pelvic mobility. Patients (n = 32, mean age: 57.4 years) due to receive THA surgery participated in the study. Measures of pelvic tilt were captured simultaneously using the device and radiograph in three functional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In measuring from four points in the IMU sensor, the average errors in a Lat , a Long , b Lat , and b Long were acceptable (1.6°-3.4°) in comparison with errors or variations (2°-10°) provided in previous studies (2, 19,22). Lewinnek et al proposed 10°of margin in inclination and an anteversion of cup position in THA as a safe zone (2).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In measuring from four points in the IMU sensor, the average errors in a Lat , a Long , b Lat , and b Long were acceptable (1.6°-3.4°) in comparison with errors or variations (2°-10°) provided in previous studies (2, 19,22). Lewinnek et al proposed 10°of margin in inclination and an anteversion of cup position in THA as a safe zone (2).…”
Section: Discussionmentioning
confidence: 82%
“…Lewinnek et al proposed 10° of margin in inclination and an anteversion of cup position in THA as a safe zone ( 2 ). Wang et al demonstrated seventy-five percent of the errors across all measurements were within 5° of the radiograph measurements ( 19 ). Kalteis et al showed that the precision of acetabular cup inclination and anteversion were 3° and 10° with plain X-rays, while those were approximately 2° with CT-scan ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMUs can provide a series a repeated measurements which may give a more representative picture of a patient’s functional pelvic tilt rather than the single ‘snapshot’ provided by current radiographic methods. A recent study we conducted has shown the potential of using an IMU as a point-of-care screening tool to identify patients with high pelvic mobility who would benefit from more detailed surgical planning of implant positioning in the pre-operative setting [ 15 ]. The IMU and radiographic measurements in this previous study correlated strongly for flexed-seated (FS) position and moderately for step-up (SU) position.…”
Section: Introductionmentioning
confidence: 99%
“…However, this previous study only compared a single sample of each of the IMU and radiograph measures for each patient. In this study we capitalise on the ability to rapidly capture multiple measurements of pelvic tilt within the same patient using the IMU device and sacral device evaluated by Wang et al [ 15 ]. Compared to the single measures of pelvic tilt measured previously, here we can further evaluate the level of expected variability in a measurement through a patient repeating the same movements.…”
Section: Introductionmentioning
confidence: 99%